Stigma and health inequality experienced by ethnic minorities during the COVID-19 pandemic in a Chinese community: an implication to health policymakers - Judy Yuen-Man Siu; Judy Yuen-Man Siu; Judy Yuen-Man Siu; Judy Yuen-Man Siu; Yuan Cao; Yuan Cao; Yuan Cao; Yuan Cao; David H. K. Shum; David H. K. Shum; David H. K. Shum (Frontiers Media S.A., 2023)
IntroductionEthnic minorities are considered one of the most vulnerable groups during the COVID-19 pandemic. However, the explanatory pathway of how their disadvantaged experiences during epidemics are related to the embedded and longstanding stigmas against them and how these embedded stigmas can affect their resilience in disease outbreaks are not well understood. This study investigated the experiences of ethnic minorities in the COVID-19 pandemic, and how their experiences were related to the embedded stigma toward them.MethodsThis study adopted a qualitative approach, interviewed 25 individuals (13 women and 12 men) from ethnic minority groups residing in Hong Kong from August 2021 to February 2022 in a semi-structured format. Thematic analysis was conducted to analyze the data.ResultsThe participants were isolated and stereotyped as infectious during the COVID-19 pandemic at community and institutional levels. Their experiences did not occur suddenly during the pandemic but were embedded in the longstanding segregation and negative stereotypes toward ethnic minorities in different aspects of life before the pandemic. These negative stereotypes affected their resilience in living and coping with the pandemic.ConclusionThe participants' experiences during the COVID-19 pandemic were mostly disadvantageous and predominantly initiated by the mainstream stigmatization toward them by the local Chinese residents and government. Their disadvantaged experiences in the pandemic should be traced to the embedded social systems, imposing structural disparities for ethnic minorities when accessing social and medical resources during a pandemic. Because of the preexisting stigmatization and social seclusion of ethnic minorities in Hong Kong, the participants experienced health inequality, which stemmed from social inequality and the power differential between them and the Chinese locals. The disadvantaged situation of the participants negatively affected their resilience to the pandemic. To enable ethnic minorities better cope with future epidemics, merely providing assistance to them during an epidemic is barely adequate, but a more supportive and inclusive social system should be established for them in the long run.